Antibody Responses Following Primary Immunization with the Recombinant Herpes Zoster Vaccine (Shingrix®) in VZV Seronegative Immunocompromised Adults - Andrea Wessely; Ines Zwazl; Melita Poturica; Lukas Weseslindtner; Michael Kundi; Ursula Wiedermann; Angelika Wagner (Vaccines)
Background: Immunocompromised patients are at risk of severe varicella zoster virus (VZV) infection and reactivation. In VZV seronegative immunocompromised persons, live-attenuated VZV vaccination is contraindicated, thus the recombinant herpes zoster vaccine (rHZV) remains a safe alternative, although an off-label application. Yet, data on the induction of a VZV-specific immune response in immunocompromised individuals with VZV-specific IgG below the assay’s cut-off are only available for patients after solid-organ transplantation (SOT). Methods: We retrospectively analyzed the induction of VZV-specific IgG antibody levels after vaccination with rHZV in immunocompromised patients who previously tested anti-VZV-IgG negative between March 2018 and January 2024. Results: Of 952 vaccinees screened that received 2 or 3 doses rHZV, depending on the underlying disease, 33 patients (median age 53.0; 51.5% female) with either hematopoietic stem cell transplantation (82%) or high-grade immunosuppressive treatment (18%) fulfilled the inclusion criteria. Upon rHZV vaccination, 88% (29/33) individuals mounted a significant antibody response exceeding the assay’s cut-off level for seropositivity (p < 0.0001). We detected higher geometric mean antibody concentrations after three compared to two doses. However, 12% remained below the assay’s cut-off level and were therefore considered non-responsive. Conclusions: The rHZV is immunogenic in VZV-seronegative immunocompromised individuals and therefore presents a valid option to induce seroconversion. However, antibody testing in high-risk groups should be considered to identify humoral non- and low responders.